Unusual Respiratory Manifestations in Two Young Adults with Duchenne Muscular Dystrophy - Julie Lemay; Frédéric Sériès; Mario Sénéchal; Bruno Maranda; François Maltais (Canadian Respiratory Journal)
Adult respirologists are often involved in the evaluation and treatment of young adult patients with Duchenne muscular dystrophy. In this context, the most frequent respiratory complication is nocturnal and daytime hypoventilation related to respiratory muscle weakness. The present article describes cases of Duchenne muscular dystrophy involving two brothers, 17 and 19 years of age, respectively, who presented with less frequently reported respiratory complications of their disease: obstructive sleep apnea and Cheyne-Stokes respiration with central apnea, which were believed to be partially or completely related to congestive cardiomyopathy.